2021
DOI: 10.3390/plants10102212
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Potato Infected with the Necrotrophic Pathogen Alternaria solani

Abstract: Potato early blight is caused by the necrotrophic fungus Alternaria solani and can result in yield losses of up to 50% if left uncontrolled. At present, the disease is controlled by chemical fungicides, yet rapid development of fungicide resistance renders current control strategies unsustainable. On top of that, a lack of understanding of potato defences and the quantitative nature of resistance mechanisms against early blight hinders the development of more sustainable control methods. Necrotrophic pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…At 24 h post inoculation of A. solani infection into a potato leaf, necrosis of the first epidermal cells on the adaxial side of the leaf has been observed. Similar to our study, symptoms appeared on the backside of a leaf that had been inoculated 24 h. However, Brouwer studied A. solani infection of potato leaves only for the first 48 h, and the interaction of genes in the late stage of infection was not clear [ 14 ]. A transcriptome analysis of the genes in potato and A. solani that exhibited interactions in the early infection stage showed that cell wall-degrading enzymes and metabolic processes may be important for early A. solani infection of potato [ 14 ].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…At 24 h post inoculation of A. solani infection into a potato leaf, necrosis of the first epidermal cells on the adaxial side of the leaf has been observed. Similar to our study, symptoms appeared on the backside of a leaf that had been inoculated 24 h. However, Brouwer studied A. solani infection of potato leaves only for the first 48 h, and the interaction of genes in the late stage of infection was not clear [ 14 ]. A transcriptome analysis of the genes in potato and A. solani that exhibited interactions in the early infection stage showed that cell wall-degrading enzymes and metabolic processes may be important for early A. solani infection of potato [ 14 ].…”
Section: Discussionmentioning
confidence: 57%
“…Similar to our study, symptoms appeared on the backside of a leaf that had been inoculated 24 h. However, Brouwer studied A. solani infection of potato leaves only for the first 48 h, and the interaction of genes in the late stage of infection was not clear [ 14 ]. A transcriptome analysis of the genes in potato and A. solani that exhibited interactions in the early infection stage showed that cell wall-degrading enzymes and metabolic processes may be important for early A. solani infection of potato [ 14 ]. In our previous study, we reported that the effector proteins AsCEP112, AsCEP19 and AsCEP20, and play important roles in late-stage A. solani infection of potato leaves [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…RT-qPCR is believed the most sensitive method among DNA-based pathogen detection technologies (Ling et al, 2010;Duan et al, 2014;Moradi et al, 2014). Certain transcripts, particularly highly transcribed ones that are repetitively transcribed from the same DNA sequence, are much more abundant than their corresponding DNA under the same conidia condition (Brouwer et al, 2021). In theory, the sensitivities of RNA-based detection methods are far superior to those of DNA-based methods.…”
Section: Introductionmentioning
confidence: 99%